Balanced Chromosomal Translocations of Parents in Relation to Spontaneous Abortions (Journal of Sciences, Islamic Republic of Iran)
The most significant complication of pregnancy is recurrent miscarriage. Numerous factors have been described as associations with recurrent wastage such as: uterine abnormalities, immunological factors, endocrinologic imbalance and chromosomal defects. Cytogenetic evaluation of couples with recurrent pregnancy losses is performed on the basis of G-banding technique only after other possible etiologic factors have been excluded. The purpose of this study was to determine the frequency of balanced translocation in 153 couples who were introduced to the medical genetic laboratory by gynecologists. The prevalence of balanced chromosomal translocation was 9.8% among which 3.3% appeared with Robertsonian translocation and the remaining (6.5%) was evident with different type of balanced chromosomal rearrangement. The yield of positive results for balanced chromosomal translocation carrier was lower than that expected. With regard to the low incidence of balanced translocation in normal population and high cost and time-consumption of chromosomal analysis cytogenetic investigation should be suggested only in couples with recurrent spontaneous abortions when clinical data fail to clarify the cause